The Role of Social Media Literacy in Supporting Digital Transformation of University Learning Systems - A'zdom, Muhammad Khofidul; Asilah, Amirah Salwa (Journal of Strategy and Transformation in Educational Management, 2025)
Social media literacy has become an essential competence in higher education as universities accelerate their digital transformation efforts. This study examines how social media literacy among students and lecturers supports the effectiveness of university learning systems in digital environments. Using a mixed-methods approach, quantitative survey data were collected from Marine Engineering undergraduates, while qualitative insights were obtained from interviews with university lecturers. The findings indicate that students demonstrate varying levels of literacy across four dimensions: access, analysis, evaluation, and ethical content creation. Higher literacy levels are significantly associated with stronger digital engagement, including active participation in online discussions, effective use of learning management systems, and improved responsiveness in academic communication. Lecturers with stronger social media literacy show greater readiness to integrate digital communication tools into pedagogical practice, contributing to more interactive and connected learning environments. The study highlights that social media literacy functions not only as a technical skill but also as a strategic communication capability that supports institutional digital transformation. Implications include the need for universities to strengthen literacy programs, enhance digital pedagogy training, and develop policies that promote responsible and effective digital communication.